1998
DOI: 10.1007/s004150050181
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea in well-controlled myasthenia gravis and the effect of thymectomy

Abstract: We conducted overnight polysomnographic sleep studies of 16 patients (5 men and 11 women) with clinically well-controlled myasthenia gravis (MG). The subtypes of MG were IIA (3 patients), IIB (11 patients), IV (1 patient) and V (1 patient). Twelve patients were found on polysomnography to have obstructive and/or central types of the sleep apnoeas (SA). Their mean age was 42.4, SD 16.4 years, and the mean duration of MG was 7.4, SD 6.96 years. SA was not detected in 4 patients whose mean age was 30.8, SD 10.71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 5 publications
0
38
1
3
Order By: Relevance
“…Older patients with a higher BMI, lower TLC and abnormal daytime arterial blood gases are most vulnerable [16]. Sleep-disordered breathing and nocturnal desaturation may improve following treatment with thymectomy [17] or prednisolone [18].…”
Section: Myasthenia Gravismentioning
confidence: 99%
See 1 more Smart Citation
“…Older patients with a higher BMI, lower TLC and abnormal daytime arterial blood gases are most vulnerable [16]. Sleep-disordered breathing and nocturnal desaturation may improve following treatment with thymectomy [17] or prednisolone [18].…”
Section: Myasthenia Gravismentioning
confidence: 99%
“…Duchenne9s muscular dystrophy (DMD) [6][7][8][9][10], and myotonic dystrophy (MD) [11][12][13][14], myopathies (e.g. nemaline myopathy [15]), Guillian-Barré syndrome and myasthenia gravis [16][17][18]. Respiratory muscle weakness, apnoeas and hypopnoeas, and abnormalities of breathing pattern and ventilatory drive may all contribute to nocturnal desaturation and sleep disruption, even before daytime ventilatory failure ensues.…”
mentioning
confidence: 99%
“…Only one study reported improvement of OSA after treatment of MG, but with thymectomy. 1 Our patient represents the fi rst report of OSA resolution after treatment of anti-MuSKR-Abpositive MG.…”
Section: Discussionmentioning
confidence: 62%
“…[1][2][3] MG is often caused by acetylcholine receptor antibodies (AchR-Abs) blocking neuromuscular transmission. However, approximately 40% of MG patients who do not have AchR-Abs have anti-muscle kinase receptor antibodies (anti-MuSKR-Ab).…”
mentioning
confidence: 99%
“…Also sleep related disorders are among the clinical manifestations of MG which include sleep disordered breathing (SDB) [i.e. central sleep apnea (CSA), obstructive sleep apnea (OSA), mixed apnea (OSA and CSA), sleep-related hypoventilation or hypoxemic syndromes] [5][6][7][8][9][10], poor sleep quality, reduced sleep efficiency, reduced sleep and awakening quality, increased number of nocturnal awakenings, excessive daytime sleepiness, reduced rapid eye movement sleep (REM sleep) and altered sleep perception and dreaming [6,8,[11][12][13] and excessive limb movements during sleep [e.g. restless leg syndrome (RLS)] [14].…”
Section: Introductionmentioning
confidence: 99%